Responsivitas Ombudsman RI Perwakilan Provinsi Kalimantan Selatan dalam Menangani Laporan Maladministrasi: Responsiveness of the Ombudsman RI Representative Office of South Kalimantan Province in Handling Reports of Maladministration - Mawaddah, Supiya; Fakhsiannor, Fakhsiannor; Malawat, Sitna Hajar (Anterior Jurnal, 2025)
This research aims to determine the responsiveness of the Ombudsman of the Republic of Indonesia Representative for South Kalimantan Province in handling reports of maladministration and to identify the factors that hinder handling these reports. The research method employs a qualitative approach with a descriptive research type. Data was collected through interviews with two staff members of the Ombudsman of the Republic of Indonesia Representative for South Kalimantan Province and three reporters, observations, and documentation. The results show that the Ombudsman of the Republic of Indonesia Representative for South Kalimantan Province is very responsive in handling reports of maladministration. Based on the analysis of six indicators from Zeithaml et al. (in Rasdiana & Ramadani, 2021:255-256), which show: Ability to Respond to the Public (friendly, responsive, and communicative staff), speed of service (most reports are resolved quickly according to the SOP), accuracy of service (reports meet the expectations and procedures set), thoroughness of service (report verification is conducted meticulously), timeliness of service (most reports are resolved on time), and responsiveness to complaints (responsive to complainants’ issues). However, this research also identifies several challenges faced by the Ombudsman Representative Office in South Kalimantan Province, including limitations in human resources (HR), budget constraints, resistance from some institutions, and issues with the Complaint Resolution Management Information System (SIMPeL).